Repatriation of academics organizational support, adjustment and intention to leave - James, R.; Azungah, T. (Emerald Publishing Limited, 2019)
Purpose – This paper aims to examine the influence of academic repatriates’ perceived organizational support, adjustment and external employment opportunity on their intention to leave. Design/methodology/approach – The data were collected from Sri Lankan academics who returned to their home university after completing their work (teaching/research) abroad. The repatriates who involved in teaching and research for one or more years abroad were included in this survey. Findings – Results indicated that repatriates’ both the perceived organizational support had an important role to play in the prediction of repatriation adjustment and intention to leave. In turn, academics who adjusted to their repatriation better were highly likely to stay at their home university. In addition, repatriates’ perceived organizational support decreased their intention to leave through adjustment. In addition, when repatriates had trouble in adjustment and perceived high external employment opportunities, they reported higher intentions to leave the university than those who perceived fewer external employment opportunities. Research limitations/implications – This study relied on cross-sectional and self-reported data and was conducted with small number of sample (112). Practical implications – For the academic institutions, this study will help to clarify their role in managing repatriation adjustment and develop appropriate organizational systems that can facilitate repatriates to better adjust to their repatriation which, in turn, reduces their intention to leave. This study signifies the role of management in retaining repatriates. Originality/value – This study further contributes to the current discussion on repatriation and moves this discussion to academic repatriates. This study, particularly, discusses the issues of retaining repatriates in a Sri Lankan context as a developing country where attracting and retaining academic repatriates are more challenging tasks for universities.
Keywords: Academics; Repatriation; University; Adjustment; Intention to leave